Motives to play videogames across seven countries: Measurement invariance of the Videogaming Motives Questionnaire - Michelini, Yanina Noelia (2023)
Introduction. Gaming motives appear to be an important predictor of time spent gaming and disordered gaming. The Videogaming Motives Questionnaire (VMQ) has shown adequate psychometric properties to assess gaming motives among Spanish college students. However, the utility of this measure has not yet been explored in other cultures. This research aimed to examine the structure and measurement invariance of the VMQ across seven countries and gender groups, and to provide criterion-related validity evidence for VMQ scores. Method. College students who reported having played videogames in the last year (n = 5192; 59.07 % women) from the US, Canada, South Africa, Spain, Argentina, England, and Uruguay completed an online survey to measure time spent gaming, disordered gaming, and the VMQ. Results. Findings support a 24-item 8-intercorrelated factor model structure for the VMQ in the total sample. Our results also support configural, metric, and scalar invariance of the VMQ across gender groups and countries. Students from North America (US and Canada) scored higher on most gaming motives (except recreation and cognitive development) than students from the other countries. The correlations between VMQ and non-VMQ variables were similar across gender and countries, except in England where VMQ correlations with time spent gaming were stronger. Discussion. These results suggest that the VMQ is a useful measure for assessing gaming motives across young adults from different countries.